2021
DOI: 10.3389/fnins.2021.673600
|View full text |Cite
|
Sign up to set email alerts
|

Inborn Errors of Metabolism Associated With Autism Spectrum Disorders: Approaches to Intervention

Abstract: Increasing evidence suggests that the autism spectrum disorder (ASD) may be associated with inborn errors of metabolism, such as disorders of amino acid metabolism and transport [phenylketonuria, homocystinuria, S-adenosylhomocysteine hydrolase deficiency, branched-chain α-keto acid dehydrogenase kinase deficiency, urea cycle disorders (UCD), Hartnup disease], organic acidurias (propionic aciduria, L-2 hydroxyglutaric aciduria), cholesterol biosynthesis defects (Smith-Lemli-Opitz syndrome), mitochondrial disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 84 publications
(95 reference statements)
0
29
0
1
Order By: Relevance
“…However, it has previously been explained in terms of mitochondrial dysfunction. In ASD patients, mitochondrial dysfunction is a common metabolic disorder ( 5 ). In their study, Rossignol et al ( 26 ) argue that mitochondrial dysfunction can result in the loss of cellular integrity in specific organs, including muscle and liver, enabling the release of CK into the bloodstream, leading to increased serum levels of CK.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has previously been explained in terms of mitochondrial dysfunction. In ASD patients, mitochondrial dysfunction is a common metabolic disorder ( 5 ). In their study, Rossignol et al ( 26 ) argue that mitochondrial dysfunction can result in the loss of cellular integrity in specific organs, including muscle and liver, enabling the release of CK into the bloodstream, leading to increased serum levels of CK.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that in 2013, the prevalence of ASD was 0.7% in China ( 4 ). While ASD's pathogenesis is still unknown, recent studies have found that some ASDs may be associated with inborn errors of metabolism ( 5 ). Some metabolic disorders can only be identified by non-targeted biochemical markers ( 5 ) and serumcreatine kinase (CK) values may be one of the potential indicators to it ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, such alterations can be rescued by the oral administration of the dipeptide glycyl-tryptophan (Gly-Trp) [ 27 ], a tryptophan precursor whose absorption does not require the intestinal expression of ACE2. Additionally, human subjects bearing an SLC6A19 loss-of-function mutation develop a disorder called Hartnup disease, characterized notably by the co-occurrence of neuropsychiatric symptoms and low blood levels of neutral amino acids [ 62 , 63 ]. In addition to SLC6A19 , we also found that in SARS-CoV2-infected enterocytes, ACE2 co-regulates with several crucial genes of the dopamine/trace amines synthetic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The variant has been reported in a Saudi Arabian family, in which two affected patients with homocystinuria were homozygous for the variant inherited from unaffected heterozygous parents [157]. There are reports that children with classical homocystinuria may have isolated ASD due to cystathionine-β-synthase deficiency [158,159].…”
Section: Pancreas and Livermentioning
confidence: 99%